The Influence of Leadership Style, Training, and Work Stress on Employee Performance at PT. Sarana Megamedilab Sentosa (SMS) in Bandar Lampung - Hepiana Patmarina; Yoga Arizon Saputra (Economics and Digital Business Review, 2026)
Employee performance is essential for the success of a company, especially in the competitive and fast-changing medical equipment sector. At PT Sarana Megamedilab Sentosa (SMS) in Bandar Lampung, this study investigates how leadership approaches, training initiatives, and workplace stress contribute to employee performance. Using a quantitative design, 34 employees were sampled from a population of 51 based on Slovin's formula. Through SPSS 25 analysis, results demonstrated that employee performance is significantly affected by leadership style, training, and work stress, both individually and simultaneously. The study emphasizes that enhancing performance requires effective leadership, ongoing job-specific training, and proper management of work-related stress to maintain a productive and supportive workplace.